Rubus lentianus, a new species from Austria and Germany—another piece of the puzzle from a European hotspot of Rubus series Radula - Lepší, Martin; Lepší, Petr; Hohla, Michael; Király, Gergely (Phytotaxa, 2023)
A new nemophilous tetraploid bramble species, Rubus lentianus of the series Radula, occurring in Central Europe (Upper Austria and Lower Bavaria), is described. Deeply incised terminal leaflets of primocane leaves and a long, abruptly narrowing apex separate it from species of this series. An identification key, a distribution map, a list of revised specimens, a scan of the type specimen, pen drawings and photographs of living specimens are provided.